NFATC2 Modulates Radiation Sensitivity in Dermal Fibroblasts From Patients With Severe Side Effects of Radiotherapy - Dulong, Joshua; Kouakou, Clara; Mesloub, Yasmina; Rorteau, Julie; Moratille, Sandra; Chevalier, Fabien P.; Vinasco-Sandoval, Tatiana; Martin, Michèle T.; Lamartine, Jérôme (Frontiers in Oncology, 2020)
Although it is well established that 5% to 15% of radiotherapy patients exhibit severe side-effects in non-cancerous tissues, the molecular mechanisms involved are still poorly known, and the links between cellular and tissue radiosensitivity are still debated. We here studied fibroblasts from non-irradiated skin of patients with severe sequelae of radiotherapy, to determine whether specific basal cell activities might be involved in susceptibility to side-effects in normal tissues. Compared to control cells, patient fibroblasts exhibited higher radiosensitivity together with defects in DNA repair. Transcriptome profiling of dermal fibroblasts from 16 radiotherapy patients with severe side-effects and 8 healthy individuals identified 540 genes specifically deregulated in the patients. Nuclear factor of activated T cells 2 (NFATC2) was the most differentially expressed gene, poorly expressed at both transcript and protein level, whereas the NFATC2 gene region was hypermethylated. Furthermore, NFATC2 expression correlated with cell survival after irradiation. Finally, silencing NFATC2 in normal cells by RNA interference led to increased cellular radiosensitivity and defects in DNA repair. This study demonstrates that patients with clinical hypersensitivity also exhibit intrinsic cellular radiosensitivity in their normal skin cells. It further reveals a new role for NFATC2 as a potential regulator of cellular sensitivity to ionizing radiation.